Dental stem cell delivery through new injectable matrices for spinal cord regeneration - Viswanath, Aiswarya (2018)
Traumatic spinal cord injury (SCI) is a global health problem involving complex pathophysiological cascade and afflicts both developing and developed countries. Transplantation of Mesenchymal stem cell population such as dental stem cells (DSC) have demonstrated preclinical potential for central nervous system (CNS) repair. The work presented in this thesis has evaluated the potential of dental stem cells from apical papillae (SCAP) in combination with different biomaterials for SCI repair.